Pembelajaran Fikih Materi Shalat Berbasis Audio Visual di Madrasah Ibtidaiyah - Luluk Mukarromah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to form students' discipline in maintaining time, especially in performing prayers, as well as to strengthen the faith and improve the quality of worship of students at Madrasah Ibtidaiyah Syafi'iyah II. The focus of this study includes: (1) Planning of Islamic Jurisprudence learning on prayer material through audio-visual media for class IV students of MI Syafi'iyah II, (2) Implementation of Islamic Jurisprudence learning on prayer material using audio-visual media, and (3) Evaluation of Islamic Jurisprudence learning on prayer material for class IV students of MI Syafi'iyah II. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects were determined purposively. Data analysis uses the Miles, Huberman, and Saldana models consisting of data condensation, data presentation, and drawing conclusions. The validity of the data is tested by triangulation of sources and techniques. The results of the study show that: (1) The use of audio-visual media in learning Islamic jurisprudence on prayer material is very relevant and in accordance with the characteristics of students, (2) Active, innovative, creative, effective, and enjoyable learning can increase the spirit and enthusiasm of students, and reduce boredom in learning, and (3) Completeness of facilities and infrastructure greatly influences the success of learning evaluation, both summative, formative, input, process, and output evaluations.